2011
DOI: 10.1038/npp.2011.279
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Tract-Specific Measures of Uncinate and Cingulum in Major Depression Using Diffusion Tensor Imaging

Abstract: Previous findings suggested the role of the prefrontal cortex, hippocampus, and cingulate gyrus in major depressive disorders (MDD), but the white matter microstructural abnormalities of the fibers connecting these brain structures are not known. The purpose of this study was to test the hypothesis that white matter abnormalities are present in association fibers of the uncinate fasciculus (UF) and cingulum bundle (CB) among MDD subjects. A total of 21 MDD subjects aged between 30 and 65 years and 21 age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
111
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 54 publications
15
111
3
1
Order By: Relevance
“…20,27,30,51,70,71 Furthermore, human studies using electrical stimulation have indicated reciprocal connections between the anterior limb of the internal capsule and the dorsolateral and ventrolateral prefrontal cortex, findings consistent with anatomical tracing research in nonhuman primates. 32 The genu of the internal capsule in turn contains pyramidal fibers that connect the precentral gyrus to the motor nuclei of the cranial nerves, and also the anterior part of the superior thalamic peduncle.…”
Section: Anatomofunctional Significance Of the Cerebral Isthmussupporting
confidence: 70%
See 1 more Smart Citation
“…20,27,30,51,70,71 Furthermore, human studies using electrical stimulation have indicated reciprocal connections between the anterior limb of the internal capsule and the dorsolateral and ventrolateral prefrontal cortex, findings consistent with anatomical tracing research in nonhuman primates. 32 The genu of the internal capsule in turn contains pyramidal fibers that connect the precentral gyrus to the motor nuclei of the cranial nerves, and also the anterior part of the superior thalamic peduncle.…”
Section: Anatomofunctional Significance Of the Cerebral Isthmussupporting
confidence: 70%
“…Additionally, we consider incising the proximal superior isthmus less destructive than the anterior corpus callosum, since the former is mainly related to the ability of set shifting while the latter participates in the vital functions of memory and learning. 20,27,30,37,38,41,43,51,70,71 Undoubtedly, approaching the frontal horn through the proximal part of the superior isthmus is not an easy and straightforward procedure. It requires thorough neuroanatomical knowledge of the insular anatomy, flawless microneurosurgical technique, and proper planning of the surgical trajectory.…”
mentioning
confidence: 99%
“…The cingulum bundle integrates disparate modular brain systems involved in attention, memory, and emotion regulation, and in mood disorders, a higher directionality of water diffusion in the cingulum bundle associates with better hedonic tone (Keedwell et al, 2012), better cognitive performance (Schermuly et al, 2010), and less psychomotor slowing (Walther et al, 2012). The number of fibers within the uncinate fasciculus inversely correlated with depression severity (Zhang et al, 2012). Executive function and processing speed were correlated with anisotropy of the anterior thalamic radiation and uncinate fasciculus in late life depression (Sexton et al, 2011).…”
Section: Lithium and Gsk3-b Effects On White Matter F Benedetti Et Almentioning
confidence: 99%
“…All diffusion weighted images (32 gradient directions) were first coregistered onto the b0 images by using the automatic image registration (AIR) algorithm with affine transformation to minimize eddy currents and remove any potential small bulk motions that occurred during the scans (Zhang et al, 2012;. The diffusion directions in the diffusion gradient table were transformed by the rotation matrix calculated by AIR, to correct changes in section angulation due to coregistration.…”
Section: Image Processingmentioning
confidence: 99%